Food Safety and Quality Concerns in Bangladesh. - Saiful Islam, Md. (Tufts University. Tisch Library., 2020)
This presentation provides a compresensive review of food safety and quality in Bangladesh.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy